Awareness of Unpredictability in Economic Policy, Fiscal Decentralisation, and Innovative Approaches for the Preservation of The Environment in South Africa - ALIAMUTU, Kansilembo Freddy; MKHIZE, Msizi (PT Keberlanjutan Strategis Indonesia, 2024)
The paper aimed to examine the awareness of unpredictability in economic policy, fiscal decentralization, and innovative approaches to preserve the environment in South Africa using annual recurrence data from 1961 to 2021 in South Africa. Dynamic ordinary least squares, completely adjusted ordinary least squares, and canonical cointegration regression are used in this study. The Maki cointegration test shows how the factors maintain an equilibrium relationship throughout the period under consideration. Data from empirical results support the environmental Kuznets curve paradigm. These findings show that the environment must be compromised during the early phases of economic growth to achieve economic success (scale phase). Long-term exponential growing economies decrease pollutants by 0.162%, but a 1% increase in economic expansion raises pollutants by 0.791%, according to the environmental Kuznets curve hypothesis. Similarly, in South Africa, long-term economic globalization, as well as unpredictability in economic policy, reduce the sustainability of the environment. In contrast, long-term fiscal decentralization and sustainable development increase it. These findings have far-reaching environmental implications. The current analysis encouraged environmental penalties and funding for projects transitioning from an energy electrical utility basis to renewables.